KUALITAS TIDUR DAN ASUPAN GIZI SEBAGAI FAKTOR RISIKO OVERWEIGHT REMAJA PUTRI - Novitasari, Maryam; Anantanyu, Sapja; Lestari, Anik (Poltekkes Kemenkes Bandung, 2024)
Overweight in female adolescence can disrupt growth and increase the risk of non-communicable diseases. Many determinants of overweight include sleep quality and nutritional intake. Late-night sleep can reduce sleep quality, trigger imbalances in leptin and ghrelin hormones, increase appetite, and lead to excessive nutritional intake. The aim of this study was to determine the relationship and the magnitude of the risk between sleep quality and nutritional intake on overweight in female adolescence. This research employs a case-control design and multistage sampling technique. 160 female students participated in the study who were divided base on normal nutritional status and overweight. The research was conducted in the city of Jambi in May 2023. Sleep quality measurement used the IPAQ (Pittsburgh Sleep Quality Index) questionnaire, and nutritional intake was assessed using a 3x24-hour recall form. BMI screening was conducted before interviewing the respondents. Data analysis utilized chi-square tests and logistic regression. The chi-square test results showed a significant relationship between sleep quality, energy intake, carbohydrate intake, and protein intake with overweight (p<0.05). Sleep quality, energy intake, and carbohydrate intake simultaneously influenced overweight occurrence in female adolescence by 11.1%. Adolescents are advised to diversify carbohydrate types and increase protein portions. Physical activities should be adjusted to optimize sleep quality.